Comment & Debate: The New Wealth: The middle classes have discovered they've been duped by the super-rich: The first of a series. Never have so many of us appeared so well-off yet felt so poor - and we used to believe obscene wealth was victimless - Bunting, Madeleine (The Guardian (London), 2007)
What's slowly dawning on middle England is that they've been duped: they were sold a line - a "fair deal for hard-working families"; meanwhile, another very different scenario was unfolding. Britain became the world's billionaire playground, attracting the super-rich with such a generous tax regime that in April the IMF went so far as to define the City of London as effectively a tax haven. The wealth of Britain's top 1,000 has quadrupled since 1997 and the rate of growth is now spiralling out of control - a massive 20% jump in the past year. Tony Blair and Gordon Brown have happily presided over an unprecedented golden age of wealth accumulation in this country - on a par with the US in Gatsby's Roaring Twenties. This bizarre tolerance is revealing: huge wealth is now regarded as a fabulous spectator sport and massively enviable. It is also, most importantly, regarded as legitimate - the global economy is akin to a vast lottery, some just get lucky. The "winner takes all" has become a respectable formula of economic life, not evidence of a systemic injustice. Any other view is dismissed, in that derogatory phrase, as the "politics of envy". Peter Mandelson summed it up in 1998 with a magnificent use of adjectives: "We are intensely relaxed about people getting filthy rich." The charge sheet is being assembled. A super-elite rachets up social comparisons, leaving everyone lower down the pecking order disgruntled - the US economist Robert Frank argues that the relationship between inequality and lower rates of happiness is now well established. His new book, Falling Behind, examines the phenomenon in the US, where the middle classes are now working harder than ever to pay exorbitant mortgages on incomes that have stagnated while the wealth of the super-rich has ballooned. "Richistan" is another country, argues a Wall Street reporter assigned to cover the subject full-time in 2003: private banking, private planes, private health and education. And it's a country stuffed full of absurd opulence - watches worth hundreds of thousands, but hey, why stop at one, what about a "watch wardrobe"?